Leakage Proof, Flame-Retardant, and Electromagnetic Shield Wood Morphology Genetic Composite Phase Change Materials for Solar Thermal Energy Harvesting - Chen, Yuhui; Meng, Yang; Zhang, Jiangyu; Xie, Yuhui; Guo, Hua; He, Mukun; Shi, Xuetao; Mei, Yi; Sheng, Xinxin; Xie, Delong (Nano-Micro Letters, 2024)
An innovative class of versatile form-stable composite phase change materials (CPCMs) was fruitfully exploited, featuring MXene/phytic acid hybrid depositing on non-carbonized wood as a robust support.The wood-based CPCMs showcase enhanced thermal conductivity of 0.82 W m−1 K−1 (4.6 times than polyethylene glycol) as well as high latent heat of 135.5 kJ kg−1 (91.5% encapsulation) with thermal durability and stability throughout at least 200 heating and cooling cycles.The wood-based CPCMs have good solar-thermal-electricity conversion, flame-retardant, and electromagnetic shielding properties.